Development and performance evaluation of a two-stage cascade impactor equipped with gelatin filter substrates for the collection of multi-sized particulate matter. (1st February 2023) - Aldekheel, Mohammad; Farahani, Vahid Jalali; Tohidi, Ramin; Altuwayjiri, Abdulmalik; Sioutas, Constantinos
Abstract: This study presents the development and evaluation of a high flow rate gelatin cascade impactor (GCI) to collect different PM particle sizes on water-soluble gelatin substrates. The GCI operates at a flow rate of 100 lpm, and consists of two impaction stages, followed by a filter holder to separate particles in the following diameter ranges: >2.5 μm, 0.2–2.5 μm, and <0.2 μm. Laboratory characterization of the GCI performance was conducted using monodisperse polystyrene latex (PSL) particles as well as polydisperse ammonium sulfate, sodium chloride, and ammonium nitrate aerosols to obtain the particle collection efficiency curves for both impaction stages. In addition to the laboratory characterization, we performed concurrent field experiments to collect PM2.5 employing both GCI equipped with gelatin filter and personal cascade impactor sampler (PCIS) equipped with PTFE filter for further toxicological analysis using macrophage-based reactive oxygen species (ROS) and dithiothreitol consumption (DTT) assays. Our results showed that the experimentally determined cut-point diameters for the first and second impaction stages were 2.4 μm and 0.21 μm, respectively, which agreed with the theoretical predictions. Although the GCI has been developed primarily to collect particles on gelatin filters, the use of a different type of substrate (i.e., quartz) led to similar particle separation characteristics. The findings of the field tests demonstrated the advantage of using the GCI in toxicological studies due to its ability to collect considerable PM-toxic constituents, as corroborated by the DTT and ROS values for the GCI-collected particles which were 26.44 nmol/min/mg PM and 8813.2 μg Zymosan Units/mg PM, respectively. These redox activity values were more than twice those of particles collected concurrently on PTFE filter using the PCIS. This high-flow-rate impactor can collect considerable amounts of size-fractionated PM on water-soluble filters (i.e., gelatin), which can completely dissolve in water allowing for the extraction of soluble and insoluble PM species for further toxicological analysis. Highlights: Two-stage cascade impactor was developed and evaluated in the lab and field tests. GCI can separate PM into the following diameters: >2.5 μm, 0.2–2.5 μm, and <0.2 μm. Gelatin filters were used for the extraction of soluble and insoluble PM species. Redox activities of PM collected using GCI were more than twice those of PCIS. GCI can collect considerable redox-active PM species for toxicity assays.